BUILDING COMPANY IMAGE AND TRUST OF PROSPECTIVE HAJJ AND UMRAH PILGRIMS THROUGH PUBLIC RELATIONS STRATEGIES - Firdos, Elbina; Dermawan, Andy; Aulia, Hanna Hilyati (Multazam : Jurnal Manajemen Haji dan Umrah, 2023)
Public relations strategy in an era of increasingly rapid business growth, especially in the field of Hajj and Umrah travel agencies, which creates new problems in the form of mushrooming fraud cases. These cases raise concerns for prospective pilgrims about choosing and trusting Hajj and Umrah travel agencies. In practice, PT Freshnel Kreasindo Perkasa Yogyakarta carries out strategies to continue to stand strong amidst business competition and the rise of fraud cases so that the company's image and consumer trust can continue to be built and maintained. This research aims to find out how public relations strategies are in building the company image and trust of prospective Hajj and Umrah pilgrims at PT Freshnel Kreasindo Perkasa Yogyakarta. The theory used in this research is the PENCILS strategy theory developed by Rosady Ruslan. The research method used is descriptive qualitative. The results of this research show that PT Freshnel Kreasindo Perkasa implements the PENCILS strategy in building the image and trust of prospective Hajj and Umrah pilgrims well, while the PENCILS strategy is in the form of publications, events, news, community involvement, information or image, lobbying and negotiating, and social responsibility